Shear wave elastography of the saphenous nerve - Bedewi, Mohamed Abdelmohsen (Medicine (Baltimore), 2020)
The purpose of this study is to study sonoelastographic features of the saphenous nerve. The study included 72 saphenous nerves in 36 healthy subjects. High resolution ultrasound and Shearwave elastography were used to evaluate the saphenous nerve. Cross sectional area (CSA) and stiffness were measured. The mean CSA of the saphenous nerve was 5.7 mm(2). The mean shear elastic modulus of the saphenous nerve in the short axis was 29.5 kPa. The mean shear elastic modulus of the saphenous nerve in long axis was 29.9 kPa. The saphenous nerve elastic modulus also showed no correlation with CSA in neither the long axis nor short axis. Positive correlation between elasticity measurements in the long and short axes. Age, height, weight, and BMI showed no correlation with saphenous nerve elastic modulus in short or long axes. The elastic modulus of the saphenous nerve has been determined in healthy subjects and can serve as a reference for future assessment of the saphenous nerve before different procedures.